Adopsi XBRL, Transformasi Digital, Tax Avoidance: A Systematic Literature Review and Future Research Agenda - Sari Zawitri (Universitas Budi Luhur, 2026)
This study aims to comprehensively map the dynamic interactions between the adoption of eXtensible Business Reporting Language (XBRL), digital transformation, and tax avoidance practices. Employing a Systematic Literature Review (SLR) approach guided by the PRISMA protocol and bibliometric analysis, this study synthesizes academic literature from 2015 to 2025 to uncover the paradigm shift from mere formal compliance toward digital institutional change. Key findings highlight the paradoxical phenomenon of the